PERAN KUALITAS SDM DALAM MENINGKATKAN PENGELOLAAN PELAYANAN PENERBITAN KARTU KELUARGA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN INHIL - GUNTUR, SM; Syafrinadina, Syafrinadina; Muslimin, Haza; BADEWIN, BADEWIN (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The purpose of this research is to determine the Service Quality of Family Card Management in Population and Civil Registration Agency, INHIL. This research is classified as descriptive research with a qualitative approach. This research was held on Population and Civil Registration Agency, INHIL. The theory used to measure the quality of service is a theory proposed by Suhady (2000: 25), the dimensions of service quality include accuracy, speed, hospitality and expense. The data used are primary data and secondary data. The data retrieval and collection were done through observations, interviews, and documentations. The data analysis was conducted by collecting data, data presentation, and conclusion. The results of this research indicate that the quality of service with accuracy indicator has shown a good condition, while the speed indicator, hospitality and expense indicators need to be improved or are in unsatisfactory condition.